Renal Artery Outcomes After Open Repair of Suprarenal or Type IV Thoraco-abdominal Aortic Aneurysms. (November 2020) - Hostalrich, Aurélien; Porterie, Jean; Segal, Jean; Lebas, Benoit; Matray, Lauranne; Abaziou, Thimothée; Ricco, Jean-Baptiste; Chaufour, Xavier
Abstract : Objective: The aim of this study was to evaluate the mid and long term patency of elective renal artery reconstructions during open surgical repair of suprarenal aortic aneurysms (SRAA) and type 4 thoraco-abdominal aortic aneurysms (T4AAA). Methods: This retrospective, single centre study included all consecutive patients who underwent surgery for SRAA or T4AAA between January 2009 and December 2019 at Toulouse University Hospital. All patients underwent strict pre-operative planning with computed tomography angiography (CTA) and 3D reconstruction of the aortic aneurysm, visceral and renal artery anatomy to choose the most appropriate surgical technique for each case. Primary patency, primary assisted patency, and rates of re-intervention were calculated using the Kaplan–Meier method. Results: In total, 103 patients, having undergone 159 renal artery revascularisation procedures, were enrolled in the study. Fifty-five patients presented with a type T4AAA and 48 patients with a SRAA. In hospital mortality was 2.9%. In association with aortic surgery, 100 direct re-implantation (62.8%), 48 retrograde bypasses (30.1%), and 11 anterograde bypasses (6.9%) of the renal arteries were performed. Median follow up was 45.9 ± 36 months. Renal artery primary patency rates were 99.4%, 96.4%, and 93.1% at one, three, and five years, respectively. Assisted primary patency rates were 99.4%, 97.7%, and 97.7% at one, three, and five years, respectively, with five cases of renal stenosis > 70% successfully treated by renal stenting. No significant difference in patency was found regarding the type of renal revascularisation. Conclusion: This retrospective study suggests that the mid term patency of elective open renal artery reconstruction during SRAA and type T4AAA surgery preceded by pre-operative planning with 3D-CTA reconstruction, yields excellent outcomes whatever the technique used.